Clustering representative days for power systems generation expansion planning: Capturing the effects of variable renewables and energy storage. (1st November 2019) - Scott, Ian J.; Carvalho, Pedro M.S.; Botterud, Audun; Silva, Carlos A.
Highlights: Demonstrate importance of incorporating storage and ramping dynamics in clustering. Improve expansion planning model accuracy by 61% with adjusted cluster weights. Weights allow accurate modelling of total energy, peak demand, and ramp dynamics. Incorporate ramping challenges to clustering approaches improving results. Demonstrate under-representation of energy storage without ramping challenges. Abstract: Decision makers rely on models to make important regulatory, policy, and investment decisions. For power systems, these models must capture (i) the future challenges introduced by the integration of large quantities of variable renewable energy sources and (ii) the role that energy storage technologies should play. In this paper, we explore several different approaches to selecting representative days for generation expansion planning models, focusing on capturing these dynamics. Further, we propose a new methodology for adjusting the outputs of clustering algorithms that provides three advantages: the targeted level of net demand is captured, the underlying net demand shapes that define ramping challenges are accurately represented, and the relationship between annual energy and peak demand is captured. This weighting methodology reduces the magnitude of the error in the representative day based generation expansion planning models estimation of costs by 61% on average. The results also demonstrate the importance of carefully performing the clustering of representative days for both system costs and technology mix. In most cases improvements to the total cost of different representative day based expansion plans are realised where conventional generation capacity is substituted for energy storage. Based on the energy storage technology selected we conclude this capacity is being used to address ramping challenges as opposed to shifting renewable generation from off to on peak periods, reinforcing the importance of capturing detailed intraday dynamics in the representative day selection process.